Evolocumab for treating primary hypercholesterolaemia and mixed dyslipidaemia: an evidence review group perspective of a NICE single technology appraisal - Carroll, Christopher; Tappenden, Paul; Rafia, Rachid; Hamilton, Jean; Chambers, Duncan; Clowes, Mark; Durrington, Paul; Qureshi, Nadeem; Wierzbicki, Anthony S. (Springer International Publishing, 2017)
As part of its single technology appraisal (STA) process, the UK National Institute for Health and Care Excellence (NICE) invited the manufacturer of evolocumab (Amgen) to submit evidence on the clinical and cost effectiveness of evolocumab. The appraisal assessed evolocumab as monotherapy or in combination with a statin with or without ezetimibe, or in combination with ezetimibe (without statin therapy), in adult patients with primary hypercholesterolaemia (which includes mixed dyslipidaemia), for whom statins do not provide optimal control of their low-density lipoprotein cholesterol (LDL-C) levels and/or for whom statins are contraindicated or not tolerated. The School of Health and Related Research Technology Appraisal Group at the University of Sheffield was commissioned to act as the independent Evidence Review Group (ERG). The ERG produced a critical review of the evidence for the clinical and cost effectiveness of the technology based on the company’s submission to NICE. The evidence was derived mainly from four randomised controlled trials comparing evolocumab with either ezetimibe or placebo in adults with primary familial or non-familial hypercholesterolaemia, who were either able to take statins or who were statin intolerant. The clinical-effectiveness review found that evolocumab is efficacious at lowering LDL-C but that there was uncertainty regarding its impact on cardiovascular disease (CVD) outcomes. In response to the ERG’s critique of the submitted health economic model, the company submitted an amended model, which also included a patient access scheme (PAS). Based on this, the deterministic incremental cost-effectiveness ratios (ICERs) for evolocumab against ezetimibe were above £74,000 and £45,000 per quality-adjusted life-year (QALY) gained within the non-familial primary and secondary prevention populations, respectively, whilst the ICER within the heterozygous familial hypercholesterolaemia (HeFH) population was approximately £23,000 per QALY gained. The final determination was that evolocumab would be a clinically and cost-effective use of UK NHS resource in certain patient subgroups.